Fate of Listeria monocytogenes in murine peritoneal macrophage subpopulations. - Harrington-Fowler, L (1982)
Peritoneal macrophages derived from CD-1 and C57BL/6 mice were separated into distinct groups based on their buoyant densities on discontinuous gradients of Percoll and assayed for antibacterial activity against Listeria monocytogenes. Subpopulations of peritoneal macrophages derived from Listeria-immune mice present a wide variation in their ability to control intracellular infection. Distinct subsets were found which exhibited bacteriostatic and listericidal activity. The fractionation procedure yielded a population of peroxidase-positive macrophages which were devoid of antilisterial action. Subpopulations of resident and elicited macrophages were also functionally heterogeneous in their ability to restrict intracellular growth of bacterial. In some experiments, subclasses were examined for secretion of plasminogen activator and phagocytosis of latex particles. These activities varied considerably with the status of activation of the macrophages, but failed to correlate with antimicrobial activity within given subpopulations.